Sebuah Adobe Flash CS6 dalam Menghitung Luas dan Keliling Bangun Datar Pada Anak Diskalkulia - Sella Malinda; Mega Iswari; Jon Efendi (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
This research is based on the problems that appear in the field, that is children with dyscalculia in grade V SDN 08 Surau Gadang Padang who have problems in mathematics about calculate area and perimeter of plane figures. This research used quasi experimental design with one group pretest-posttest design type. The result of this study were obtained based on data analysis seen from pretest and posttest score. The data were processed using mann whitney test. For n1 = 5 and n2 = 5 at 95% significant level and α = 0,05 obtained Uhit = 0 and Utab = 4. The null hyphotesis is accepted because Uhit ≤ Utab. The use media-based learning adobe flash CS6 is not effective in improve ability to calculate area and perimeter of plane figures for children with dyscalculia in grade V SDN 08 Surau Gadang Padang.